The Effect of Live Streaming Interaction on Consumers' Purchase Intention in Bandung City: Social Presence as a Mediation Factor - Luki Ramdani; Rita Komaladewi; R Thomas Budhayawan Yudha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the digital era, live streaming has emerged as a widely used marketing strategy across e-commerce platforms. Social presence—defined as the perceived sense of social interaction during live streaming—is believed to significantly influence consumers’ purchase intentions. However, limited research has explored the link between live streaming, social presence, and purchase intention. This study addresses that gap by examining the impact of live streaming on purchase intention and the mediating role of social presence. A quantitative approach was employed, using a questionnaire distributed to e-commerce users who frequently watch live streaming. A purposive sampling method yielded 330 respondents. Data were analyzed using Structural Equation Modeling with SmartPLS 3.0, including tests for convergent and discriminant validity, reliability, R², Q², and hypothesis testing. The results indicate that live streaming positively affects purchase intention, and social presence significantly mediates this relationship. These findings suggest that enhancing social presence through live streaming can effectively increase consumer purchase intention. For businesses, this highlights the importance of interactive elements such as real-time communication, authentic content, and exclusive offers. The study is limited to 330 respondents from Bandung and focuses on Generation Y and Z, which may limit the generalizability of the results. Additionally, it considers only social presence as a mediating variable, excluding other possible mediators.